2019
DOI: 10.1038/s41598-019-55243-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced microscopy analysis of the micro-nanoscale architecture of human menisci

Abstract: The complex inhomogeneous architecture of the human meniscal tissue at the micro and nano scale in the absence of artefacts introduced by sample treatments has not yet been fully revealed. The knowledge of the internal structure organization is essential to understand the mechanical functionality of the meniscus and its relationship with the tissue’s complex structure. In this work, we investigated human meniscal tissue structure using up-to-date non-invasive imaging techniques, based on multiphoton fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…Furthermore, hypertrophy in meniscus due to increased proteoglycan content is closely related to increased disorganization of collagenous structure and decreased collagen content 8,19,20 . Recent studies have reported that circumferential collagen bundles in radial cross-section are organized as polygons in a honeycomb-like shape with a diameter of 0.6-1mm 29,30 . Each polygon includes smaller compartments with circular pores inside them and gaps between each polygon to allow fluid flow through the meniscus .…”
Section: J O U R N a L P R E -P R O O F Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hypertrophy in meniscus due to increased proteoglycan content is closely related to increased disorganization of collagenous structure and decreased collagen content 8,19,20 . Recent studies have reported that circumferential collagen bundles in radial cross-section are organized as polygons in a honeycomb-like shape with a diameter of 0.6-1mm 29,30 . Each polygon includes smaller compartments with circular pores inside them and gaps between each polygon to allow fluid flow through the meniscus .…”
Section: J O U R N a L P R E -P R O O F Resultsmentioning
confidence: 99%
“…include two-dimensional polarized light microscopy (PLM) 12,34,35 , 3D advanced microscopy such as multiphoton microscopy and second-harmonic generation microscopy 16,29,30 and small angle x-ray diffraction techniques 36 . However, all of these techniques are limited to 5 to 60 µm thin tissue sections, losing the real 3D information because a single collagen fiber averages between 5-10 µm in diameter and collagen fiber bundles together are even larger 11,13 .…”
Section: Previously Established Methods For the Characterization Of Cmentioning
confidence: 99%
“…15 The three dimensional structure of the ''honeycomb-like'' compartments have been recently observed in fresh and untreated human meniscal samples. 32 The authors detected ''honeycomb-like'' compartment of size varying from micro (25 to 100 lm) to macro (600 lm to 1 mm). Each honeycomb compartment is discovered to be filled by pores.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mechanical behaviour such as stiffness of anisotropic biological tissues which are composed of directional fibres e.g. meniscal tissue [28] is known to be affected by the directionality of fibres [29]. Therefore, a deeper understanding of the effect of tissue microstructural features is needed to predict the local response of the system to external infusion and physiological processes; what is the effect of fibre bundle orientation on hydraulic permeability?…”
Section: Introductionmentioning
confidence: 99%